Comparison of Real-Life Systems of Care for ST-Segment Elevation Myocardial Infarction - Surya Dharma (Ubiquity Press, 2020)
The success of ST-segment elevation myocardial infarction (STEMI) networks application in Europe and the United States in delivering rapid reperfusion therapy in the community have become an inspiration to other developing countries to develop regional STEMI network in order to improve the STEMI care. Although barriers are found in the beginning phase of constructing the network, recent analysis from national or regional registries worldwide have shown improvement of the STEMI care in many countries over the years. To improve the overall care of patients with STEMI particularly in developing countries, improvements should be focusing on how to minimize the total ischemia time, and this includes care improvement at each step of care after the patient shows signs and symptoms of chest pain. Innovation in health technology to develop the electrocardiogram transmission and communication system, along with routine performance measures of the STEMI network may help bridging the disparities of STEMI system of care between guideline recommended therapy and the real world clinical practice.